The term of «Public Diplomacy» its role and functions (Herald of Journalism, 2020)
Public diplomacy – a tool for longterm action rarely lets achieve de sirable in certain situations, but to create a favorable climate for foreign policy in general. Under public diplomacy meant different things at times, and it is not possible to develop a comprehensive balanced strategy.Public diplomacy is promoting national interests and ensure national security by examining attitudes of foreign public opinion, informing it and the impact on those who view it generates. Public diplomacy is mainly aimed at a mass audience. It proceeds from the assumption that public opinion can have a significant influence on their governments and political systems. Any kind of public diplomacy aimed at a specific audience, this audience uses the appropriate language and imagery. It allows her to achieve the intended policy objectives.
Keywords: diplomacy, communication, policy.